DEGREES OF ENTREPRENEURIAL INTENT AND ENTREPRENEURIAL ORIENTATION AT DIFFERENT STAGES OF ENTREPRENEURSHIP EDUCATION (Proceedings of the International Conference on Education, 2025)
Entrepreneurship has been popular among young population of every country. They want to be their own boss, independent from any control and self-made millionaires. Many universities offer entrepreneurship program either in the form of series of courses within an establish management programs or as a separate program/department. However, there was a lack of report on efficiency of such program on the graduates.  At Bangkok University’s School of Entrepreneurship and Management (BUSEM), there is a separate entrepreneurship program comprising courses targeting business idea generation, business plan creating, business pitching and launching, and business review. In this research we evaluated the efficacy of the program by employing Entrepreneurial Intent (EI) and Entrepreneurial Orientation (EO) that were the indices usually used to understand degrees of desire and ability to be an entrepreneur. This research followed BU’s 1,500+ entrepreneurship students for 8 years (2016-2024) and found that years of study (Year) was the influential factor to both EI and EO among BUSEM students. However, among the EI scales, only reversed EI3 (wanting to work as employee in large organization) was significantly impacted by Year and FB separately. For EO, Year significantly influenced the scores of many EO scales; EOI2 (ready to run the project by new method), EOP1 (readiness to confront with the problem), EOP2 (ready to run the project by new method) and EOR2 (love to make bold investment of time and money); meanwhile, only EOI4 (solve the problem by new method) was significantly influenced by FB. Therefore, the BUSEM’s Entrepreneurship curriculum led to a gradual increase in Entrepreneurial Orientation toward the final years of the program.   The challenges for the educators were to maintain the EI scores for the students and enhance EO level for the young entrepreneurs.
Keywords: Entrepreneur; Entrepreneurial Intent; Entrepreneurial Orientation; Entrepreneurship Education; Entrepreneurship Curriculum